“Da Kabbalah à Pachamama” : percursos criativos de um autor fronteiriço - Monteiro, Glaucos Luis Flores (2024)
This doctoral thesis examines my artistic practice (from the beginning of the Cuiabana rock band Kabbalah, in the 1980s, to the present day when I seek a sound more linked to ancestral, indigenous and South American sounds) seeking to understand how the influences came about and crossings of indigenous music in this musical practice; To achieve this, the first step was to discover what this indigenous music is in our current Brazilian context. The research uses Deleuzian Cartography as a methodological direction, accepts the suggestion of Epistemic Disobedience from decolonial authors, and also fits into the proposal of Southern Epistemologies (as described by Boaventura de Sousa Santos) by assuming the practice of Ecology of Knowledge in the artistic experiment. The empirical part of the experiment involves a central authorial composition called “From Kabbalah to Pachamama”, presented at several events since 2021, in conjunction with popular social movements. The work has an artistic research part (with regard to the work Da Kabbalah à Pachamama), but it also consists of an analysis of my artistic production, that is, in the first part it is a research on art and, in another part, research through art. The results obtained, through the empirical part, responded positively to the initial, tested and investigated hypothesis that asked: is there indigenous Brazilian music? So yes, there is a wide range of contemporary indigenous musical production, with various accents (among which the author also fits), genres, degrees of ancestry, and adapted for current social networks.